Stability and bioactivity of nanocomplex of TNF-related apoptosis-inducing ligand - Na, Seong Ju; Chae, Su Young; Lee, Seulki; Park, Kyeongsoon; Kim, Kwangmeyung; Park, Jae Hyung; Kwon, Ick Chan; Jeong, Seo Young; Lee, Kang Choon (ELSEVIER SCIENCE BV, 2008)
The tumor necrosis factor-related apoptosis inducing ligand (TRAIL) has gained much attention due to its potent therapeutic effect for cancer and rheumatoid arthritis. In this Study, we attempted to develop the injectable formulations which can stabilize TRAIL and thus show prolonged blood circulation in vivo. The positively charged TRAIL was mixed with hyaluronic acid (HA), resulting in the formation of nanocomplexes. The zeta-potentials of nanocomplexes and their mean diameters were significantly dependent on the feed ratio of HA to TRAIL. The increase in the feed ratio of HA reduced the particle size and decreased the value of the zeta-potential. The bioactivity of TRAIL in the complexes was comparable to that of native TRAIL, indicating that the complex formation did not affect the activity of TRAIL. Furthermore, the stability of TRAIL in the complexes was retained for 6 days, during which the bioactivity of native TRAIL disappeared. When native TRAIL was subcutaneously injected into the rats, its plasma concentration was not detectable after 12 h. In contrast, for HA/TRAIL nanocomplexes in 1% HA solution, substantial amount of TRAIL was circulated in blood for up to 5 days. These results imply that HA-based formulations of TRAIL hold the potential as the therapeutics. (c) 2008 Published by Elsevier B.V.
Keywords: HUMAN GROWTH-HORMONE; IN-VIVO; PEGYLATED LIPOSOMES; SOLVENT EXCHANGE; DRUG-DELIVERY; MICROSPHERES; CANCER; FORMULATION; INDUCTION; MICROENCAPSULATION